2019
DOI: 10.5214/ans.0972.7531.260104
|View full text |Cite
|
Sign up to set email alerts
|

Anti-brain cancer activity of chloroform and hexane extracts of Tinospora cordifolia Miers: an in vitro perspective

Abstract: Background: Plants have been suggested as safest source of therapeutic agents, with multi targeted mode of action and least side effects. Tinospora cordifolia, commonly known as Guduchi in India, is one of the most highly valued herbs in Ayurvedic medicine. It possesses potential anti-cancer, anti-inflammatory, hepatoprotective, anti-diabetic, immune-stimulatory and various other beneficial activities. Purpose: The present study was aimed to investigate the differentiation inducing potential of chloroform and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In a study by Thippeswamy and Salimath, TCE inhibited cell proliferation and decreased ascites secretion in Ehrlich ascites tumor (EAT) mice [63]. Anti-tumor effects of TCE are very well reported in various cancer cell lines as well as in mice models [64][65][66]. DL bearing mice also show an alteration in lymphoid organs such as reduction in thymus, enlargement of spleen and lymph nodes [67].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Thippeswamy and Salimath, TCE inhibited cell proliferation and decreased ascites secretion in Ehrlich ascites tumor (EAT) mice [63]. Anti-tumor effects of TCE are very well reported in various cancer cell lines as well as in mice models [64][65][66]. DL bearing mice also show an alteration in lymphoid organs such as reduction in thymus, enlargement of spleen and lymph nodes [67].…”
Section: Discussionmentioning
confidence: 99%
“…Tinospora cordifolia (TCE) has a strong ability to resist metastasis and induce differentiation in neuroblasts, and IMR-32 cells can be induced by treatment with higher concentrations of TCE. Studies have shown that TCE or phytochemicals derived from this plant can be used as safe pharmacological agents together with conventional drugs [ 146 , 147 ]. Chlorogenic acid (CA) is a plant compound isolated from Eucommia ulmoides , honeysuckle and other plants.…”
Section: Other Tumorsmentioning
confidence: 99%
“…They also prevent the cell migration and inhibit the expression of Neural cell adhesion molecule (NCAM). Diterpeniod lactones such as tinocordin, columbin, 8-hydroxycolumbin, and 10-hydroxycolumbin are reported to be in the chloroform extracts from T. cordifolia stems [61]. The methanol extract and berberine isolated from T. cordifolia exert potential antitumor activity against HCA-7 cells (human colon adenocarcinoma cell line).…”
Section: Anti-cancer Activitymentioning
confidence: 99%